Work Environment and Empowerment on Craftsmen Productivity at The Furniture Industry Center in Lumajang - Hartono Hartono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The human aspect holds an important role in sustainability and development of the company because basically every company activity is never separated from the human element. Production, marketing and technology activities cannot run without being carried out by humans. Both large and small companies, in the human resource approach means each organization or company must be able to create a sense of secure and satisfaction so that the human resources in work environment become competitive. The objective of this study is to determine the effect of work environment and empowerment on craftsmen productivity at Furniture Industry Center in Karangbendo village, Lumajang. The independent variables are work environment and empowerment. The dependent variable is productivity. The respondent of the study are craftsmen at Furniture Industry Center in Karangbendo village, Lumajang with a sample of 30. By using multiple linear regression analysis technique, the results obtained that the work environment has a significant effect on productivity, the empowerment has no significant effect on productivity while simultaneously the work environment and empowerment have significant effect on productivity. The 51.3% of productivity can be explained by work environment and empowerment variables and the remaining 48.7% was affected by other variables that not examined in this study.